Pemanfaatan FIy Ash Sebagai Substitusi Semen Dan Batu Gamping Sebagai Agregat Pada Beton - Windi Desliono; Herman Parung; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
FIy Ash is a waste combustion combustion system and one of the pozzolanic mixed minerals found in Indonesia. An environmentally friendly concrete technology innovation to reduce the use of cement and river stone, namely utilizing FIy ash as a substitute for cement and limestone as an aggregate for concrete mixtures. This study aims to see the mechanical properties of concrete and the optimum proportion of FIy ash in the concrete mixture with limestone as coarse aggregate. The percentage of FIy ash used varies, namely 0%, 10%, 15%, and 20%. Concrete compressive strength testing is carried out when the concrete is 7 days, 21 days, and 28 days old with a compressive strength plan of 25 MPa. For the flexural strength and split tensile strength test, it is carried out when the concrete is 28 days old. The research used 48 cylinders 150 x 300 mm, 12 beams measuring 150 x 150 x 600 mm, carried out at the Laboratory of Civil Engineering Structures, PauIus Christian University of Indonesia, Makassar. The observation results show that the influence of FIy ash as a substitute for cement with limestone aggregate for concrete, produces concrete with compressive strength, flexural strength, and tensile strength, the maximum is 27.56 MPa, 2.50 MPa, respectively. and 4.68 MPa for normal concrete with the optimum use proportion of FIy ash 15%.